ESPEN guideline on ethical aspects of artificial nutrition and hydration. Issue 3 (June 2016) - Druml, Christiane; Ballmer, Peter E.; Druml, Wilfred; Oehmichen, Frank; Shenkin, Alan; Singer, Pierre; Soeters, Peter; Weimann, Arved; Bischoff, Stephan C.
Summary: Background: The worldwide debate over the use of artificial nutrition and hydration remains controversial although the scientific and medical facts are unequivocal. Artificial nutrition and hydration are a medical intervention, requiring an indication, a therapeutic goal and the will (consent) of the competent patient. Methods: The guideline was developed by an international multidisciplinary working group based on the main aspects of the Guideline on "Ethical and Legal Aspects of Artificial Nutrition" published 2013 by the German Society for Nutritional Medicine (DGEM) after conducting a review of specific current literature. The text was extended and introduced a broader view in particular on the impact of culture and religion. The results were discussed at the ESPEN Congress in Lisbon 2015 and accepted in an online survey among ESPEN members. Results: The ESPEN Guideline on Ethical Aspects of Artificial Nutrition and Hydration is focused on the adult patient and provides a critical summary for physicians and caregivers. Special consideration is given to end of life issues and palliative medicine; to dementia and to specific situations like nursing care or the intensive care unit. The respect for autonomy is an important focus of the guideline as well as the careful wording to be used in the communication with patients and families. The other principles of Bioethics like beneficence, non-maleficence and justice are presented in the context of artificial nutrition and hydration. In this respect the withholding and withdrawing of artificial nutrition and/or hydration is discussed. Due to increasingly multicultural societies and the need for awareness of different values and beliefs an elaborated chapter is dedicated to cultural and religious issues and nutrition. Last but not least topics like voluntary refusal of nutrition and fluids, and forced feeding of competent persons (persons on hunger strike) is included in the guideline.